National Violent Death Reporting System, 2004 ([Verlag nicht ermittelbar], 2006)
The National Violent Death Reporting System (NVDRS) collects data on violent deaths, i.e., suicides, homicides, and legal intervention, including terrorism-related incidents. The system also includes some other types of deaths, namely deaths due to undetermined intent and unintentional deaths due to firearms. One of the main reasons for including these types of deaths is that there is overlap in how these deaths are coded. For example, a particular poisoning case may be classified as an undetermined death in one state, but in a neighboring state, the same case may be coded as a suicide or an unintentional poisoning. NVDRS is an incident-based system that collects data from different data sources, including death certificates, coroner and medical examiner records, police reports, crime lab data, and child fatality review records. The system collects data on a violent incident, the deaths belonging to that incident, the injury mechanisms leading to death, and the alleged perpetrators (suspects) involved in the violent incident. The relationship of the victim to the suspect is also recorded, as are the relationships of each person to the injury mechanisms included. State health departments participating in NVDRS typically identify relevant violent deaths as their death certificates are filed and then establish the details of the cases from medical examiner, coroner, and law enforcement records. Data collection is ongoing as the source documents from the different data providers become available at different times and intervals. The data represent the violent incidents that occurred between January and December of that data year as submitted by the participating states.